Игра ферзей - Гулевич Александр Михайлович (Боевая фантастика, 2019)
Экземпляры: Аб-т (20250128) / Инвентарный номер: 50799 / Цена: 160.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Г 94 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445